Association Between Handgrip Strength and Cardiovascular Disease Risk in MASLD: A Prospective Study From UK Biobank - Tae Seop Lim; Sujin Kwon; Sung A. Bae; Hye Yeon Chon; Seol A. Jang; Ja Kyung Kim; Chul Sik Kim; Seok Won Park; Kyoung Min Kim (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background This study aimed to investigate the association between handgrip strength (HGS) and cardiovascular disease (CVD) in individuals with metabolic dysfunction‐associated steatotic liver disease (MASLD) using data from the UK Biobank cohort. Methods A total of 201 563 participants were enrolled in this study. The HGS was measured using a Jamar J00105 hydraulic hand dynamometer. MASLD was defined as the presence of hepatic steatosis accompanied by one or more cardiometabolic criteria. Hepatic steatosis was identified using a fatty liver index ≥ 60. Advanced liver fibrosis was defined by a fibrosis‐4 (FIB‐4) score > 2.67. To examine the differences in the incidence of CVD, male and female participants were divided into non‐MASLD, MASLD with high HGS, MASLD with middle HGS, and MASLD with low‐HGS groups. Results Of the study participants, 75 498 (37.5%) were diagnosed with MASLD, with a mean age of 56.5 years, and 40.6% were male. The median follow‐up duration was 13.1 years. The frequency of incident CVD events increased significantly across groups: 10.9% in non‐MASLD, 13.3% in MASLD with high HGS, 14.8% in MASLD with middle HGS, and 18.4% in MASLD with low HGS for males (p < 0.001). In females, the frequency of incident CVD events was 6.1% in non‐MASLD, 9.2% in MASLD with high HGS, 10.7% in MASLD with middle HGS, and 13.3% in MASLD with low HGS (p < 0.001). Using the non‐MASLD group as a reference, multivariate‐adjusted hazard ratios (HRs) (95% confidence intervals [CI]) for CVD varied according to HGS in individuals with MASLD. In males with MASLD, HRs (95% CI) were 1.03 (0.96–1.10) for high HGS, 1.14 (1.07–1.21) for middle HGS, and 1.38 (1.30–1.46) for low HGS; in females with MASLD, they were 1.07 (0.97–1.18) for high HGS, 1.25 (1.14–1.37) for middle HGS, and 1.56 (1.43–1.72) for low HGS. The incidence of CVD events increased as HGS decreased in participants with MASLD, regardless of the presence or absence of advanced liver fibrosis (all p < 0.001). Conclusions This large prospective cohort study using the UK Biobank showed that in MASLD, a decrease in HGS was associated with increased CVD risk.